The important dimensions for assessing organization's readiness toward business intelligence systems from the perspective of Malaysian organization - H. Anjariny, Ahmed; Zeki, Akram M. (2013)
Nowadays, Business Intelligence (BI) is becoming as a necessity for a lot of organizations. Figures show that billions of US dollars are spent on BI systems annually. Unfortunately, according to statistics, more than half of BI projects are ending with unrealized benefit. Many researchers tried to investigate the reasons behind this failure rate, they found one the main reasons is that many organizations are not yet ready for such systems. Therefore, it is highly encouraged to assess organization’s readiness toward BI systems to avoid any losses and to enhance the overall revenue. At the same time, it was noticed that although many studies have been done, but none of them were done empirically on Malaysian context. So, an initiative has been taken, by the authors, to develop a model for assessing organization's readiness toward BI systems, based on the context of Malaysian Organizations (CMOs). This paper will uncover some results of the first round survey of this study. A brief introduction on BI systems and the challenges of their implementation will be presented. In addition, a review and analysis of models for assessing organizations’ readiness toward BI systems is provided.